Cost Oriented Tele-Controlled Service Robot for Increasing the Quality of Life of Elderly and Disabled - ROBCO 18. Issue 30 (2018) - Chivarov, Nayden; Chikurtev, Denis; Markov, Emanuil; Chivarov, Stefan; Kopacek, Peter
Abstract: This article presents the service robot ROBCO 18 and how it is designed to be cost-oriented. The purpose of ROBCO 18 is to support elderly and disabled, acting as a personal home assistant. The robot will be able effectively to assist people in their homes. The robot is designed to be cost-oriented, using low-cost devices and components. Robot control software has been developed to allow various interfaces and control methods to be used. The robot software system optimizes and distributes data from the robot's sensors and actuators. In this way, elderly and disabled people are safe in handling the robot and can choose their convenient method of robot control. Finally, we conducted experiments with elderly people to test how the robot is performing different tasks. As a conclusion usability review of the Cost Oriented Tele-Controlled Service Robot for Increasing the Quality of Life of Elderly and Disabled -ROBCO 18 is presented.